2019
DOI: 10.1155/2019/3692605
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Bioactivity Evaluation ofEryngium planumandCnicus benedictusPolyphenolic-Rich Extracts

Abstract: This study evaluated the biological activities of Eryngium planum and of Cnicus benedictus extracts enriched in polyphenols obtained by nanofiltration. The HPLC-MS analysis showed that E. planum contains mainly flavonoids, especially rutin, while in C. benedictus extracts show the high concentration of the phenolic acids, principally the chlorogenic acid and sinapic acid. Herein, there is the first report of ursolic acid, genistin, and isorhamnetin in E. planum and C. benedictus. C. benedictus polyphenolic-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
3
28
2
Order By: Relevance
“…There are no reports of catechin and quercetin in extracts of this species of Eryngium caucasicum Trautv. However, Paun et al [50] identify quercetin and chlorogenic acid in the ethanolic extract of Eryngium planum [50], and Marcetik et al [51] detect catechin and chlorogenic acid in the root methanolic extract of E. palmatum [51]. In comparison to their reports, both avonoids including catechin and quercetin were higher in aqueous extract than in ethanolic extract in our study.…”
Section: Discussioncontrasting
confidence: 85%
“…There are no reports of catechin and quercetin in extracts of this species of Eryngium caucasicum Trautv. However, Paun et al [50] identify quercetin and chlorogenic acid in the ethanolic extract of Eryngium planum [50], and Marcetik et al [51] detect catechin and chlorogenic acid in the root methanolic extract of E. palmatum [51]. In comparison to their reports, both avonoids including catechin and quercetin were higher in aqueous extract than in ethanolic extract in our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Total polyphenol content of the extract was 1.36 mg GAE/g. Paun et al extracted aerial parts of Eryngium planum in 50% ethanol with water ( v / v ) [ 21 ]. The obtained extract was subjected to lipoxygenase inhibition testing and showed high inhibitory activity with an IC 50 value of 31.30 µg/mL.…”
Section: Lipoxygenase Inhibition By Plant Extracts Of Family Apiacmentioning
confidence: 99%
“…Ethanolic extract of Cnicus benedictus investigated by Paun et al also showed very good ability of lipoxygenase inhibition (IC 50 = 52.70 µg/mL) [ 21 ]. Total flavonoid content in extract was 0.47 mg QE/mL and total phenolic content was 2.65 mg GAE/mL.…”
Section: Lipoxygenase Inhibition By Plant Extracts Of Family Astermentioning
confidence: 99%
“…38 Microfiltration and nanofiltration processes can be used to prepare extracts with substantially higher polyphenol content, DPPH scavenging activity and ferric reducing power. 39 Other therapeutic properties…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…53 An abundance of triterpenoids, including a-amyrenone, a-amyrin acetate, a-amyrine and multiflorenol acetate have also been reported. 39 Additionally, the levels of tannins in C. benedicta extracts have been found to be as high as 8%. 54 The lignans trachelogenin, nortracheloside and artigenin are also present in relative abundance in C. benedicta extracts, 55 together with lower levels of flavonoids 56 and essential oils.…”
Section: Phytochemistrymentioning
confidence: 99%